Relationship between the Optical Properties and Chemical Composition of Urban Aerosol Particles in Lithuania - Julija Pauraite; Kristina Plauškaitė; Vadimas Dudoitis; Vidmantas Ulevicius (Advances in Meteorology, 2018)
In situ investigation results of aerosol optical properties (absorption and scattering) and chemical composition at an urban background site in Lithuania (Vilnius) are presented. Investigation was performed in May-June 2017 using an aerosol chemical speciation monitor (ACSM), a 7-wavelength Aethalometer and a 3-wavelength integrating Nephelometer. A positive matrix factorisation (PMF) was used for the organic aerosol mass spectra analysis to characterise the sources of ambient organic aerosol (OA). Five OA factors were identified: hydrocarbon-like OA (HOA), biomass-burning OA (BBOA), more and less oxygenated OA (LVOOA and SVOOA, respectively), and local hydrocarbon-like OA (LOA). The average absorption (at 470 nm) and scattering (at 450 nm) coefficients during the entire measurement campaign were 16.59 Mm−1 (standard deviation (SD) = 17.23 Mm−1) and 29.83 Mm−1 (SD = 20.45 Mm−1), respectively. Furthermore, the absorption and scattering Angström exponents (AAE and SAE, respectively) and single-scattering albedo (SSA) were calculated. The average AAE value at 470/660 nm was 0.97 (SD = 0.16) indicating traffic-related black carbon (BCtr) dominance. The average value of SAE (at 450/700 nm) was 1.93 (SD = 0.32) and could be determined by the submicron particle (PM1) dominance versus the supermicron ones (PM > 1 µm). The average value of SSA was 0.62 (SD = 0.13). Several aerosol types showed specific segregation in the SAE versus SSA plot, which underlines different optical properties due to various chemical compositions.